GAMBARAN SANITASI RUMAHTERKAIT DENGAN LEPTOSPIROSIS (STUDI DI KECAMATAN GAJAH MUNGKUR KOTA SEMARANG) - Endang Setiyani (Jurnal Kesehatan Masyarakat (Undip), 2016)
The Gajah Mungkur sub-district in Semarang City has highest leptospirosis cases (reported with seven infected and one died) in year 2015. The highest number found in Petompon and Sampangan village. The purpose of this study is to understand the house sanitation with leptospirosis, include: there are piles of used stuffs, a place to store food, uncovered trash, roof ceiling, secured windows, and wide ventilation. This research used cross sectional design survey and observational method. Samples in this study amounted to 77 houses. The observation of house sanitation recorded on the observation sheet. Data analyzed using distribution frequency and bivariate chi square test. The results shownthere are piles of used stuffs (89.6%); places to store food (74.0%); uncovered trash (80.5%); roof ceiling (85.7%); secured window (88.3%); and wide ventilation (87.0%). Suggestion for people in Petompon and Sampangan village to covered trash, to keep food in place with anti-rat, clean up a piles of used stuffs from being used as nest for breeding, andclose the vents.